2019
DOI: 10.24917/20845596.12.3
|View full text |Cite
|
Sign up to set email alerts
|

Zachowania zdrowotne studentów kierunków nauczycielskich

Abstract: Zachowania zdrowotne są uznawane za jedne z podstawowych determinantów zdrowia. Nauczyciel, obok rodziców, odgrywa ważną rolę w kształtowaniu pozytywnych zachowań zdrowotnych u dzieci i młodzieży, dlatego studenci studiów nauczycielskich powinni prezentować prozdrowotny styl życia. Celem badań przedstawionych w niniejszym artykule było zdiagnozowanie poziomu deklarowanych przez studentów kierunków nauczycielskich pozytywnych zachowań mających związek ze zdrowiem. Badania prz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Students of other majors showed lower levels of health-friendly behaviors and physical activity [8]. As for the comparison of medical students to students of teacher education programs, as the ones who should also promote a healthy lifestyle with their attitude, a study from Lublin of 2019 showed that 14% of the students surveyed had never played sports, and less than 20% of the respondents declared undertaking daily physical activity [10]. According to the Lublin study, students regularly sleeping 6-7 hours a day accounted for about 39% of the respondents, and in the case of the study discussed in this paper it was about 52.3%.…”
Section: Discussionmentioning
confidence: 99%
“…Students of other majors showed lower levels of health-friendly behaviors and physical activity [8]. As for the comparison of medical students to students of teacher education programs, as the ones who should also promote a healthy lifestyle with their attitude, a study from Lublin of 2019 showed that 14% of the students surveyed had never played sports, and less than 20% of the respondents declared undertaking daily physical activity [10]. According to the Lublin study, students regularly sleeping 6-7 hours a day accounted for about 39% of the respondents, and in the case of the study discussed in this paper it was about 52.3%.…”
Section: Discussionmentioning
confidence: 99%